2015
DOI: 10.4236/ns.2015.710048
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Noise Pollution in Ado-Ekiti Metropolis Using Mobile Phone

Abstract: Noise is considered as the most pervasive pollutant, it constitutes the most disturbing among the city pollutants and is a serious urban crisis in Ado Ekiti metropolis. Noise pollution was monitored at five different locations in Ado-Ekiti, the capital town of Ekiti State of Nigeria. The study was done using a Virtual Instrument; a Sound Pressure Level mobile application installed on a mobile phone. The equivalent noise level using A-weighting was taken every fifteen minutes in each location between 6:00 am an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The negative effects of noise pollution are multifarious to human health. These include annoyance, insomnia, low productivity at work, permanent ringing or buzzing in the ears (tinnitus), sleep disturbance and fatigue, psychological stress and stress related disease, psychological changes in heart beat and increased blood pressure (Dawal et al, 2007;Akinkuade and Fasae, 2015). The most conspicuous effect of noise pollution is damage to human hearing ability which may be temporary or permanent depending on the exposure time ( , 2002;Sheetal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects of noise pollution are multifarious to human health. These include annoyance, insomnia, low productivity at work, permanent ringing or buzzing in the ears (tinnitus), sleep disturbance and fatigue, psychological stress and stress related disease, psychological changes in heart beat and increased blood pressure (Dawal et al, 2007;Akinkuade and Fasae, 2015). The most conspicuous effect of noise pollution is damage to human hearing ability which may be temporary or permanent depending on the exposure time ( , 2002;Sheetal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The finding is reflective of the medical prevalence of sicknesses in Jos noticed during visitation to some hospitals in Jos such as; Plateau State Specialist Hospitals and Jos University Teaching Hospitals. Okokon et al [12], Ogunseye et al [2] and Akinkuade et al [13], reported that, long-term exposure to excessive road traffic noise and other noise-generating sources has many negative effects on human health and wellbeing such as hypertension, disturbed sleep, deafness, nervousness, breakdown, mental disorder, high blood pressure, headaches, dizziness, inefficiency, insomnia, and impaired cognitive development in children. Also, Cai et al [15] reported that excessive noise exposure could be so severe to the extent that either a permanent loss of memory or a psychiatric disorder might occur.…”
Section: Effect Of Road Traffic Noise On Human Health and Wellbeingmentioning
confidence: 99%
“…Long exposure to excessive road traffic noise and other noisegenerating sources has many adverse effects on human health and wellbeing [12]. For instance, excessive road traffic noise exposure may cause deafness, nervousness, breakdown, mental disorder, high blood pressure, headaches, dizziness, inefficiency, and insomnia [13]. Similarly, Dasarathy et al [14] reported that even a relatively low level of noise adversely affects human health.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found out that Eight (8) hours and beyond daily exposure to noise level ranging from 64.8 dBA to 98.0 dBA caused hearing impairments. Traffic was the major source of noise identified with others like music studios, night clubs, generators, construction sites and religious activities [10,11]. Oyedepo et al [5] analysed noise pollution in Illorin metropolis, Nigeria and showed that at 56 to 98 dBA, discomfort and irritation were experienced by inhabitants which also reduced productivity.…”
Section: Residential Areasmentioning
confidence: 99%